Executive Summary of Gainesville's Urban Forests in 2016 - Michael G. Andreu; Caroline A. Hament; David A. Fox; Robert J. Northrop (EDIS, 2019)
This 2-page fact sheet written by Michael G. Andreu, Caroline A. Hament, David A. Fox, and Robert J. Northrop and published by the UF/IFAS School of Forest Resources and Conservation describes a 2016 ecological assessment of the urban forest in the city of Gainesville, FL. It provides a detailed look into some of the economic and ecological values of the forest to enhance understanding and improve urban forest policies, planning, and management, as well as to provide empirical data for the inclusion of trees within environmental regulations. https://edis.ifas.ufl.edu/fr417